Community-based Approaches to Creating Adaptive Solutions for Urban Challenges: Two Case Studies (EAAE Joint Publishings, 2026)
Addressing diverse social, environmental, cultural, and economic urban challenges requires understanding them as dynamic, complex systems. This paper presents ongoing research within the Baltimore Social-Environmental Collaborative (BSEC), a U.S. Department of Energy Urban Integrated Field Laboratory (IFL). Focused on Baltimore as a midsized U.S. industrial city grappling with equitable solutions to climate change and social injustice, BSEC involves diverse collaborators. It adopts an iterative collaborative cycle relating regional climate trends and other factors with environmental and social priorities to inform community-guided equitable climate solutions. This paper highlights two projects within BSEC’s knowledge co-creation process. The first addresses energy poverty, employing spatial statistical techniques and mapping to investigate the spatial distribution of energy burden and provide insight into the social injustice in energy access. The second uses field surveys, computation, and community engagement to develop a data-driven decision-making approach to integrating Blue-Green Infrastructure (BGI). The paper concludes with an overview of engagement methods important to BSEC and informative for other architectural researchers.